2003
DOI: 10.1002/jmv.10307
|View full text |Cite
|
Sign up to set email alerts
|

IgG antibodies to human papillomavirus 16, 52, 58, and 6 L1 capsids: Case‐control study of cervical intraepithelial neoplasia in Japan

Abstract: In Japan, human papillomavirus (HPV) 16, 52, and 58 are most commonly associated with cervical intraepithelial neoplasia (CIN). By contrast, HPV6 is primarily associated with genital warts. This study was designed to evaluate the association between IgG antibody responses to common HPVs and the risk of CIN development within a Japanese population. CIN cases (n = 141) and controls (n = 109) were tested for cervical HPV DNA and serum IgG antibodies to L1 capsids of HPV16, 52, 58, and 6. Seropositivity to HPV16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
7
5
0
Order By: Relevance
“…In contrast to the low HPV-16 prevalence, we found that HPV-6 seroprevalence was 31 % among controls, which was higher than among controls in many other casecontrol studies (Silins et al, 1999;Matsumoto et al, 2003). The frequency of controls infected by HPV-18 was essentially similar to other case-control studies (Combita et al, 2003;Silins et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast to the low HPV-16 prevalence, we found that HPV-6 seroprevalence was 31 % among controls, which was higher than among controls in many other casecontrol studies (Silins et al, 1999;Matsumoto et al, 2003). The frequency of controls infected by HPV-18 was essentially similar to other case-control studies (Combita et al, 2003;Silins et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…The low exposure level of HPV-16 infection among controls in this study is likely to reflect the fact that HPV-16 is a rare sexually transmitted infection in Taiwan. Liaw et al (1995) analysed 261 cytologically normal women from the same cohort and found that only 0.8 % were HPV DNA positive for the high-risk HPV types 16, 18, 31 or 45.In contrast to the low HPV-16 prevalence, we found that HPV-6 seroprevalence was 31 % among controls, which was higher than among controls in many other casecontrol studies (Silins et al, 1999;Matsumoto et al, 2003). The frequency of controls infected by HPV-18 was essentially similar to other case-control studies (Combita et al, 2003;Silins et al, 1999).…”
mentioning
confidence: 51%
“…In our study, not surprisingly, presence of HPV 16 antibody to VLPs correlated strongly to presence of HPV 16 DNA ( P = 0.0004) and not with other HPV genotypes when compared to HPV DNA–negative samples. These data show Australian women have similar trend to other studies that have evaluated HPV seropositivity in patients with CIN (18–20) . These data further highlight that serologic tests will not identify HPV 16–associated CINs in women with negative HPV DNA.…”
Section: Discussionsupporting
confidence: 79%
“…One explanation for this difference is that the antibody adjustment may reflect residual confounding by HPV, since only 54% of CIN cases were seropositive for HPV16/52/58 due to the limited sensitivity and high type-specificity of HPV capsid serology (Matsumoto et al, 2003). Another reasonable explanation is that smoking and C. trachomatis infection may be significant cofactors associated with persistent HPV infections.…”
Section: Discussionmentioning
confidence: 99%
“…We examined HPV DNA in cervical samples by polymerase chain reaction (PCR) using consensus primers for the HPV L1 region (Yoshikawa et al, 1999). Detection of IgG antibodies to HPV16, 52 and 58, the most frequently detected HPV types in Japan, was performed by enzyme-linked immunosorbent assay (ELISA) using purified L1-capsids (virus-like particles (VLPs)) as antigens (Matsumoto et al, 2003). In addition, the level of IgG antibodies to Chlamydia trachomatis was determined by using an enzyme immunoassay (EIA) kit (Thermo Labsystems, Vantaa, Finland) that does not detect antibody to Chlamydia pneumoniae.…”
Section: Methodsmentioning
confidence: 99%